Mixed mid-term review for German traffic light coalition in the energy transition: Significant effort needed to achieve targets - Wolf-Peter Schill; Alexander Roth; Adeline Guéret; Felix Schmidt (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
December 13, 2023 - The German traffic light coalition began its term two years ago with ambi- tious energy policy goals. Halfway through the legislative period, its track record is mixed. Good progress has been made in some areas, but in others a large gap between targets and the status quo remains. The Ampel-Monitor Energiewende by the German Institute for Economic Research (DIW Berlin) shows where we stand today in terms of key technologies for the transition to climate neutrality. This brief study first provides an overview of various indicators, followed by a detailed look at the dynamics of individual developments. While Germany is making good progress with photovoltaics, for example, the expansion of onshore wind power is currently well below the tar- get path. Progress in electromobility is also clearly too slow. Overall, the pace of the energy transi- tion must be significantly increased to meet Germany's climate protection commitments. However, if the government increases its efforts and acts consistently, the targets can still be achieved.
Keywords: 330